Our experience with enteric ileal perforation: a retrospective study at a tertiary care centre in northern India - Agrawal, Puneet; Imbisat, M. Zaid (International Surgery Journal, 2019)
Background: Typhoid fever is one of major causes of intestinal perforation in India and is one of the common surgical emergencies for which intervention is required. The study aims to evaluate the clinical presentation, operative findings, outcome of surgical procedures, postoperative complications and associated mortality among the patients managed for typhoid ileal perforation in a tertiary care hospital. Methods: This was a retrospective study evaluating the patients who were operated for typhoid ileal perforation peritonitis in FH Medical College, Agra, UP, India between April 2017 and September 2019. Diagnosis of typhoid ileal perforation was made with the combination of clinical presentation, laboratory investigations, radiological results and per-operative findings. Results: In the present study, 57 patients were managed for typhoid ileal perforation. Majority of the patients were young. In our study 40 patients (70.18%) were male and 17 patients (29.82%) were female. All patients presented with pain in abdomen and abdominal distension. However there was no history of fever in 19.3% of patients. Free gas under the right diaphragm was present in 60% of patients. Exploratory laparotomy was done in all the patients and multiple perforations were found in 59.65% of patients. Ileostomy was made in 75% of patients. Most common post-operative complication was wound infection (85.96%) and mortality was 12.28%. Conclusions: Perforation peritonitis is an alarming complication of typhoid fever which needs urgent and aggressive management. Mortality rate is high (12.28%) and may be attributed to delayed presentation.